When and Why Worry About Real Exchange Rate Appreciation? : The Missing Link Between Dutch Disease and Growth. (IMF Working Papers; Working Paper ;, 2010)
We review the literature on Dutch disease, and document that shocks that trigger foreign exchange inflows (such as natural resource booms, surges in foreign aid, remittances, or capital inflows) appreciate the real exchange rate, generate factor reallocation, and reduce manufacturing output and net exports. We also observe that real exchange rate misalignment due to overvaluation and higher volatility of the real exchange rate lower growth. Regarding the effect of undervaluation of the exchange rate on economic growth, the evidence is mixed and inconclusive. However, there is no evidence in the literature that Dutch disease reduces overall economic growth. Policy responses should aim at adequately managing the boom and the risks associated with it.